VIRGIL'S CARTHAGINIANS AT AEN. 1.430–6: CYCLOPES IN BEES' CLOTHING. (30th April 2014) - Giusti, Elena
Abstract : Virgil's poetry has long been recognised as delving into a poetics of comparison which employs sudden shifts from the miniature to the gigantic. So too have Virgilian similes long been singled out as a privileged locus where complex inter- and intra-textual allusions serve to highlight the primary role that these similes play in the narrative and poetic context of Virgil's work. Along these lines, this paper addresses one such simile at Aene.d 1.430–6, where the Tyrians building Carthage are compared to busy bees working at their hive. The paper explores the impact that the recognition of the simile's inter- and intra-textual connections may have on the interpretation of the scene of Aeneas' arrival at Carthage, and on certain long-debated aspects of the poem as a whole.